PENGARUH MOTIVASI KERJA TAMTAMA KRI KELAS PATTIMURA KOARMADA I TERHADAP KINERJA PRAJURIT DALAM MELAKSANAKAN KESIAPAN OPERASI - Trisandya Palanda; Ari Sukmana (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Motivation is very important in improving soldier performance, work motivation of soldiers needs to be raised so that soldiers can carry out performance with the best results. Conversely soldiers who do not have high motivation in doing their jobs will find it difficult to work well and tend to be irresponsible even if the soldier has very good abilities. If the work motivation of the soldiers can be built, the soldiers can have a better performance for the organization in terms of carrying out operational readiness. The purpose of the research is to analyze and prove the effect of work motivation on the performance of the KRI enlisted class Pattimura in carrying out operations readiness. The research method used in this study is a quantitative method with data analysis using SPSS (statistical package for the social sciences) while the sample in this study amounted to 77 enlisted KRI Pattimura class. Data collection techniques were carried out by distributing questionnaires to respondents, as well as literature studies. he results of the study indicate that there is a significant influence of work motivation variables on the performance of soldiers on board, this can be seen from the t count of 12.092 greater than t table 1.992. For the coefficient of determination (R Square) regression of 0.661, shows that work motivation partially significantly influences the performance of the soldiers by 66.1%.